PERANCANGAN USER INTERFACE PADA WEBSITE SD AL FALAH (ASSALAM) MENGGUNAKAN METODE USER CENTERED DESIGN (UCD) - Aldica Febrin S Dewiyani Sunarto Tan Amelia (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
One of the open services SD Al Falah (Assalam) is a website with the address www.sdalfalahassalam.sch.id. This website is to provide information to students, guardians of students or prospective students. The contents of the SD Al Falah (Assalam) website are about achievements, the latest news, alumni, assignments, agenda, work, info and registration of new students. Based on the analysis of the answers to the questionnaire, the website display needs to be updated and designed because the conclusions obtained from the results of the questionnaire do need to be redesigned because there is an assessment of improvement criteria that show low priority (Saverity Rating value). To overcome this problem, research is conducted to prove the website and provide a new design based on the results of the evaluation that will be done. One method that can be used to analyze web sites is User Centered Design (UCD), which uses the user's website as a primary consideration in creating a website. The final result of this research is to design a user interface with language prototyping. Judging from the final evaluation data and the priority improvement intervals used in the conformity rating table, users assess that the new UI is easier to learn than the old design. UI usability evaluations carried out before and after development, UI, make, on average, an increase of 1.16 which means there are no problems.